15+11c=5-18+18c

Simple and best practice solution for 15+11c=5-18+18c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15+11c=5-18+18c equation:


Simplifying
15 + 11c = 5 + -18 + 18c

Combine like terms: 5 + -18 = -13
15 + 11c = -13 + 18c

Solving
15 + 11c = -13 + 18c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-18c' to each side of the equation.
15 + 11c + -18c = -13 + 18c + -18c

Combine like terms: 11c + -18c = -7c
15 + -7c = -13 + 18c + -18c

Combine like terms: 18c + -18c = 0
15 + -7c = -13 + 0
15 + -7c = -13

Add '-15' to each side of the equation.
15 + -15 + -7c = -13 + -15

Combine like terms: 15 + -15 = 0
0 + -7c = -13 + -15
-7c = -13 + -15

Combine like terms: -13 + -15 = -28
-7c = -28

Divide each side by '-7'.
c = 4

Simplifying
c = 4

See similar equations:

| -25=3(7n+4) | | x-9=-3x+27 | | y=18x+3 | | -6w-3=-7w-18 | | 4(z+5-24)=5z-13 | | 6x+7x=72 | | (2+yi)*(x-3i)=7-i | | 13b=-12+16b | | 7+6(1w-3)=31 | | -v-10=10-6v | | 5j-10+9j=5+9j | | -14+3x=x | | 6a+7b=19 | | 3x-10=2x+20 | | 5(1a-4)=44 | | 4s=5s+6 | | 3(x-2)=2x+3+x | | X^2-25x+256=0 | | 18=2[x+6] | | 10p=6+7p | | 5x+50=-95 | | g+10=-9g | | a=15-b | | 8n-10=10n+10 | | x=-27+-2.25y | | ab=56 | | 3x-4+2y= | | 2(a-2)=49(2a-4) | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+2) | | -3q-8=10-5q | | -8z+8=-7z | | 1t^2-300t+45000= |

Equations solver categories